2001
DOI: 10.1074/jbc.m005126200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of the Protein/Lipid Complexes Associated with Pore Formation by the Bacterial Toxin Pneumolysin

Abstract: Pneumolysin, a major virulence factor of the human pathogen Streptococcus pneumoniae, is a soluble protein that disrupts cholesterol-containing membranes of cells by forming ring-shaped oligomers. Magic angle spinning and wideline static 31 P NMR have been used in combination with freeze-fracture electron microscopy to investigate the effect of pneumolysin on fully hydrated model membranes containing cholesterol and phosphatidylcholine and dicetyl phosphate (10:10:1 molar ratio). NMR spectra show that the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
1
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 28 publications
0
58
1
1
Order By: Relevance
“…The two long helices in the ESAT-6 hairpin structure formed by residues Phe8 to Trp43 and Glu49 to Ala79 are indeed twice the length required to insert into a lipid bilayer. A number of studies showed the importance of cholesterol in protein-lipid interactions in bacterial infection processes (2,13,17). Although our results suggest that both cholesterol and PC are needed for membrane interaction of ESAT-6, under different experimental conditions, the presence of PC alone has shown some effect (18,29).…”
Section: Discussioncontrasting
confidence: 49%
“…The two long helices in the ESAT-6 hairpin structure formed by residues Phe8 to Trp43 and Glu49 to Ala79 are indeed twice the length required to insert into a lipid bilayer. A number of studies showed the importance of cholesterol in protein-lipid interactions in bacterial infection processes (2,13,17). Although our results suggest that both cholesterol and PC are needed for membrane interaction of ESAT-6, under different experimental conditions, the presence of PC alone has shown some effect (18,29).…”
Section: Discussioncontrasting
confidence: 49%
“…4E, Movies S9 and S10). The ability of pneumolysin to cause blebbing has been documented before (43). We also used rotenone (inhibiting mitochondrial complex I) or azide (inhibiting complex IV) (see SI Materials and Methods) to show that ATP depletion does not prevent PFNinduced vesiculation (Movies S11, S12, S13, and S14).…”
Section: Resultsmentioning
confidence: 99%
“…Since it is a pore-forming toxin, membraneinteraction and assembly therein are the key steps, associated with its mechanism of action. Recently membrane interaction of several protein and peptide toxins like pneumolysin (37), Vibrio cholerae cytolysin (38), equinatoxin (39), E. coli ␣-hemolysin (40, 41) B. thuringiensis ␦-toxin (31, 42) and pardaxin (21) have been studied in detail in order to understand their mechanism of action. Although, pore-formation has been demonstrated by electrophysiological experiments (4, 7) and visualized by electron microscopy (10) Both the Wild Type and Mutant Peptides Derived from the Leucine Zipper-like Motif Bind to the Phospholipid Membrane-In order to detect the ability of the peptides to bind to phospholipid vesicles, they were labeled by fluorescent probe NBD.…”
Section: Resultsmentioning
confidence: 99%